2016
DOI: 10.1080/15374416.2016.1188702
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Effects of Problematic Social Networking on Adolescent Psychopathology: The Mediating Role of Sleep Disruptions

Abstract: Concerns are growing about adolescents' problematic social networking and possible links to depressed mood and externalizing behavior. Yet there remains little understanding of underlying processes that may account for these associations, including the mediating role of sleep disruption. This study tests this putative mediating process and examines change in problematic social networking investment and disrupted sleep, in relation to change in depressed mood and externalizing behavior. A sample of 874 students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 73 publications
3
67
0
1
Order By: Relevance
“…As a topic of current interest to a wide audience, research findings in this area are also being widely discussed in a public forum and as socially responsible researchers, we must consider the impact of our words. For example, research literature often approaches media use as a potential threat or harmful activity, using language around social media "addiction" and "problematic use" [10,[72][73][74][75][76][77][78][79], which can pathologise social media use despite insufficient evidence for considering it an addiction [80]. From our experience through research and engagement with adolescents and their teachers and parents, we have found that this type of language from adults is not constructive and often shuts down the potential for meaningful dialogue that can build shared inter-generational understanding.…”
Section: "Teenagers These Days"mentioning
confidence: 99%
“…As a topic of current interest to a wide audience, research findings in this area are also being widely discussed in a public forum and as socially responsible researchers, we must consider the impact of our words. For example, research literature often approaches media use as a potential threat or harmful activity, using language around social media "addiction" and "problematic use" [10,[72][73][74][75][76][77][78][79], which can pathologise social media use despite insufficient evidence for considering it an addiction [80]. From our experience through research and engagement with adolescents and their teachers and parents, we have found that this type of language from adults is not constructive and often shuts down the potential for meaningful dialogue that can build shared inter-generational understanding.…”
Section: "Teenagers These Days"mentioning
confidence: 99%
“…[12][13][14][15] Sleep interventions for today's adolescents must therefore address social media habits as part of supporting sufficient, good quality sleep, which may also bring about associated improvements in school experiences and mental health. 16,17 In order to effectively support healthy social media habits for sleep, we first need to understand the cognitive, emotional and social drivers that underpin adolescents' bedtime social media engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, communicating via mobile phones "into the night" likely contributes to sleep problems, which in turn may lead to increases in a wide range of psychosocial problems-from mental health symptoms to poor coping and self-esteem. Indeed, a body of research has documented negative consequences of excessive use of other electronic media (Hale & Guan, 2015;Vernon, Barber, & Modecki, 2015;Vernon et al, 2017), and we argue these negative effects may be due, in part, to technology's potential for replacing other tasks necessary for healthy development, such as sleep.…”
mentioning
confidence: 95%